THE EFFECT OF ORGANIZATIONAL CULTURE ON WORK ETHICS IS MEDIATED BY MOTIVATION IN EMPLOYEES OF PT INDUSTRI NABATI LESTARI KEK SEI MANGKEI KAB. SIMALUNGUN - Aritonang, Oka; Siregar, Liper; Butarbutar, Marisi; Efendi, Efendi; Sherly, Sherly (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2025)
The objective of this research is to examine how organizational culture affects employee motivation. This study aims to ascertain how employee work ethics are impacted by motivation. The unit of analysis in this research is 127 permanent employees. The analysis was conducted with qualitative and quantitative analysis. The findings demonstrated that both the impact of motivation on employee work ethics and company culture had a favorable and substantial relationship. Motivation acts as a mediating variable between the influence of organizational culture on work ethics. Keywords: organizational culture, motivation, work ethics, and employees.